LOGISTIC BASICS FOR CONTROL OF ENTERPRISE MATERIAL RESOURCES - D. N. Trukhanovich (Наука и техника)
Integration function of logistics in other words vision of manufacture as a process that reveals and satisfies material requirements of consumers by means of manufacturing goods and providing services makes up logistic basics for control of various processes at an enterprise. Creation of a logistic control system by streams of material values on the basis of the process approach, balanced attitude of needs and readiness of realization of material value deliveries and also definition of service quality allows to retain values of financial assets "connected" in the stocks on a minimum level that leads in its turn to decrease in cost price of production and increase of its competitiveness.